Review on Omphalitis in Neonates of Ruminants - Tawfiq, Mohammad Munir (Journal of Natural Sciences – Kabul University, 2025)
Omphalitis, or umbilical infection, is the cellulitis of the umbilicus and its surrounding tissues, mostly affecting calves, lambs, and kids. Omphalitis typically occurs within 2-3 days of parturition and can cause severe morbidity and mortality. Different factors, such as infectious agents, mechanical causes, immune system failure to control the infection, and poor sanitation, play roles as causative agents. Affected animals show signs such as enlargement of the umbilicus, pain, pus secretion, hernia, and abscess formation. The diagnosis of omphalitis is made based on clinical signs and ultrasonographic examination. Broad-spectrum antibiotics can be administered to treat affected animals. In some cases, such as hernia, surgical correction is advisable. This review discusses the causes, pathogenesis, clinical signs, diagnosis, and treatment of omphalitis in neonates of ruminants.